Bi-reforming of Methane with Steam and CO2 over Ni/La-SBA-15 Catalyst for Synthesis Gas Production - Singh, Sharanjit; Vo, Dai-Viet N. (International Conference on Catalysis (iCAT 2016), 2016)
Bi-reforming of methane with steam and CO2 has been emerged as an alluring reforming technique for syngas production with a desirable H2/CO ratio close to 2, which is highly compatible for the industrial generation of methanol and Fischer-Tropsch chemicals. This study focuses on preparation, physicochemical attributes and the catalytic performance of 10%Ni/La-SBA-15 catalyst for the combined steam and dry reforming of methane. The La2O3-incorporated mesoporous silica support (La-SBA-15) previously prepared by one-pot hydrothermal method was doped with Ni(NO3)2 precursor solution using an incipient wetness impregnation approach to synthesize a 10%Ni/La-SBA-15 catalyst. Various characterization techniques including XRD, FTIR, BET, HR-TEM, H2-TPR and TPO measurements were employed to investigate the physicochemical properties of both fresh and spent catalysts. Bi-reforming of methane was carried out in a tubular fixed-bed reactor under atmospheric pressure at 923 K – 1023 K and CH4:CO2:H2O = 2:1:1 with gas hourly space velocity (GHSV) of 36 L gcat-1 h-1. Although La-SBA-15 support possessed high BET surface area of 737.3 m2 g-1, an unavoidable decline in surface area with Ni metal addition to 535.4 m2 g-1 for 10%Ni/La-SBA-15 catalyst was evident indicating the diffusion of NiO nanoparticles into the mesopores of La-SBA-15 support. Indeed, H2-TPR result shows that NiO particles present on support surface were reduced to metallic Ni0 phase at 675 K, while NiO species inhabited inside the mesoporous channels of support were completely reduced at higher reduction temperature of above 750 K due to strong metal-support interaction. Additionally, the presence of NiO phase with small average crystallite size of 17.4 nm was confirmed by X-ray diffraction measurement. The 10%Ni/La-SBA-15 catalyst exhibited stable activity and selectivity during the span of 12 h on-stream regardless of reaction temperature of 923-1023 K. Methane conversion increased with growing reaction temperature from 923 to 1023 K and reached to the highest value of about 55%. Interestingly, H2/CO ratio also enhanced with rising temperature and it was always greater than 1. In addition, H2 selectivity and yield were superior to those of CO. These observations would be due to the concomitant presence of CH4 steam reforming reaction favored for H2 formation.